The perceived quality of in-vehicle auditory signals: a structural equation modelling approach. Issue 11 (2nd November 2017) - Chi, Chia-Fen; Dewi, Ratna Sari; Surbakti, Yopie Yutama; Hsieh, Dong-Yu
Abstract: The current study applied Structural Equation Modelling to analyse the relationship among pitch, loudness, tempo and timbre and their relationship with perceived sound quality. Twenty-eight auditory signals of horn, indicator, door open warning and parking sensor were collected from 11 car brands. Twenty-one experienced drivers were recruited to evaluate all sound signals with 11 semantic differential scales. The results indicate that for the continuous sounds, pitch, loudness and timbre each had a direct impact on the perceived quality. Besides the direct impacts, pitch also had an impact on loudness perception. For the intermittent sounds, tempo and timbre each had a direct impact on the perceived quality. These results can help to identify the psychoacoustic attributes affecting the consumers' quality perception and help to design preferable sounds for vehicles. In the end, a design guideline is proposed for the development of auditory signals that adopts the current study's research findings as well as those of other relevant research. Practitioner Summary: This study applied Structural Equation Modelling to analyse the relationship among pitch, loudness, tempo and timbre and their relationship with perceived sound quality. The result can help to identify psychoacoustic attributes affecting the consumers' quality perception and help to design preferable sounds for vehicles.